(untitled) (Majalah Kedokteran Bandung, 2014)
Gangguan ansietas menyeluruh merupakan bagian penting dari beban global penyakit, dan diproyeksikan sebagai penyebab kedua paling umum kecacatan pada tahun 2020. Gangguan ansietas menyeluruh menyebabkan peningkatan distres dan terganggunya fungsi kehidupan. Penelitian ini merupakan penelitian potong lintang dengan consecutive sampling pada 100 pasien klinik psikiatri Rumah Sakit dr. Pirngadi Medan selama periode 1 Juli hingga 31 Juli 2012. Pengumpulan data dilakukan melalui wawancara menggunakan kuesioner, Mini International Neuropsychiatric Interview for International Classification of Disease-10 (MINI ICD-10), dan dilanjutkan dengan kriteria diagnostik Pedoman Penggolongan dan Diagnosis Gangguan Jiwa di Indonesia III (PPDGJ III) yang digunakan di Indonesia untuk konfirmasi diagnosis. Hasil penelitian ini mengungkapkan, jumlah pasien dengan gangguan ansietas menyeluruh adalah 23%. Jumlah gangguan ansietas menyeluruh diidentifikasi lebih besar dalam kelompok subjek perempuan (14/23), menikah (13/23), dan bekerja (12/23). Simpulan, tidak ada hubungan jenis kelamin, status pernikahan, dan status pekerjaan dengan gangguan ansietas menyeluruh. Kata kunci: Gangguan ansietas menyeluruh, klinik psikiatri, MINI ICD-10 The Relationship between Gender, Marital Status, Employment Status and Generalized Anxiety Disorder in Psychiatry Clinic of dr. Pirngadi Hospital Medan Abstract Generalized anxiety disorder constitute a substantial proportion of the global burden of disease, and are projected to form the second most common cause of disability by 2020. Generalized anxiety disorder led to increased distress and impaired life functioning. This study was a cross-sectional study with consecutive sampling to 100 patients of psychiatric clinic of dr. Pirngadi hospital Medan during the period 1st July until 31th July 2012. Data was collected through interviews using questionnaire, Mini International Neuropsychiatric Interview for International Classification of Disease-10 (MINI ICD-10) form, and continued with the diagnostic criteria of Pedoman Penggolongan dan Diagnosis Gangguan Jiwa di Indonesia III (PPDGJ III) that have been used in Indonesia to confirm the diagnosis. Results of this research revealed, the number of patients with generalized anxiety disorder was 23%. The number of generalized anxiety disorder was larger identified in the groups of female’s subject, (14/23), married (13/23) and employed (12/23). In conclusion, there is no relationship between gender, marital status, employment status and generalized anxiety disorder. Key words: Generalized anxiety disorder, MINI ICD-10, psychiatric clinic DOI: 10.15395/mkb.v46n4.340